lac fusion analysis of the bet genes of Escherichia coli: regulation by osmolarity, temperature, oxygen, choline, and glycine betaine. - Eshoo, M W (1988)
The synthesis of glycine betaine, a powerful osmoprotectant, from its precursor, choline, is a function of the bet genes. The bet genes code for the high-affinity transport of choline and the enzymes for its conversion to glycine betaine. These genes map at 7.5 min on the E. coli chromosome and are contained on the conjugative plasmid F'2. To study the transcriptional regulation of the bet genes in response to various environmental conditions, a collection of 30 lac operon fusions was isolated by utilizing the bet genes contained on F'2. Four osmoregulated bet loci (betA, betB, betC, and betT) were identified based on biochemical, regulatory, and merodiploid analysis of these fusions. All of the bet fusions demonstrated a 7- to 10-fold increase in transcription in response to increases in the osmotic strength of the growth medium. Choline further induced expression of lac fusions at the betA, betB, and betT loci when the cells were grown under conditions of osmotic stress. The end product of the pathway, glycine betaine, was a corepressor of choline induction for fusions at the betA and betT loci. Expression of the betA, betB, and betT loci was reduced 7- to 10-fold under anaerobic conditions. In addition, expression of the betB and betT loci was reduced when the cells were grown in high osmolarity at 16 degrees C. These studies demonstrate that the expression of the bet genes is under the control of several environmental stimuli.